Corallinapetrales and Corallinapetraceae: A new order and family of coralline red algae including Corallinapetra gabrielii comb. nov. Issue 3 (5th April 2021) - Jeong, So Young; Nelson, Wendy A.; Sutherland, Judith E.; Peña, Viviana; Le Gall, Line; Diaz‐Pulido, Guillermo; Won, Boo Yeon; Cho, Tae Oh
Abstract : The coralline algal genus Corallinapetra is currently monospecific and was established on the species Corallinapetra novaezelandiae, known from a single collection from north‐eastern New Zealand. On the basis of multi‐gene phylogenetic analyses, Corallinapetra has been resolved apart from all currently recognized families and orders within the Corallinophycidae. We analyzed DNA sequence data from the holotype of Lithothamnion gabrielii, which has been considered a heterotypic synonym of L. muelleri, and an unidentified sample collected from Stewart Island in New Zealand, using psb A, rbc L, and COI‐5P genes. We also observed detailed morpho‐anatomical characters with light and scanning electron microscopy. Our phylogenetic analyses showed that L. gabrielii and the sample from New Zealand belonged to the same clade as Corallinapetra, distinct from other families and orders in the Corallinophycidae. Members of this clade are distinguishable from other families and orders in the Corallinophycidae by possessing sporangia that are surrounded by remnant sterile filaments that are weakly calcified in mature multiporate sporangial conceptacles that produce zonately divided tetrasporangia. Therefore, we propose that Corallinapetra be placed in its own family, Corallinapetraceae and order, Corallinapetrales, and that L. gabrielii should be assigned to Corallinapetra, as C. gabrielii, to reflect their phylogenetic relationships. We also obtained a partial rbc L sequence data from the lectotype of L. muelleri, the generitype of Lithothamnion . Comparison of the L. muelleri type sequence with L. gabrielii unambiguously demonstrated that these two species are not conspecific, and confirm the placement of L. muelleri within the Hapalidiales.